2004
DOI: 10.1158/1078-0432.ccr-0518-03
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Preclinical Pharmacokinetic and Metabolic Studies of the Combretastatin Prodrugs Combretastatin A4 Phosphate and A1 Phosphate

Abstract: Purpose: Combretastatin A4 phosphate (CA4P) and its structural analog, combretastatin A1 phosphate (CA1P), are soluble prodrugs capable of interacting with tubulin and causing rapid vascular shutdown within tumors. CA4P has completed Phase I clinical trials, but recent preclinical studies have shown that CA1P displays a greater antitumor effect than the combretastatin A4 (CA4) analog at equal doses. The aim of this study, therefore, is to compare pharmacokinetics and metabolism of the two compounds to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
72
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 10 publications
4
72
1
Order By: Relevance
“…These drug exposures are relevant for in vivo studies, where mouse plasma levels of the active CA4P metabolite CA4 were reported in the region of 0.5-2.8 lM, within 90 min of administering 100 mg/kg CA4P. 29,43 Our data confirmed several previous studies [24][25][26][27][28] showing that the mode of direct tumor cell death was anti-proliferative, leading to apoptosis, and that resistance to CA4P was indeed maintained in vivo, since markers of apoptosis, namely DNA fragmentation and cleaved caspase-3 expression were significantly greater in SW1222…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These drug exposures are relevant for in vivo studies, where mouse plasma levels of the active CA4P metabolite CA4 were reported in the region of 0.5-2.8 lM, within 90 min of administering 100 mg/kg CA4P. 29,43 Our data confirmed several previous studies [24][25][26][27][28] showing that the mode of direct tumor cell death was anti-proliferative, leading to apoptosis, and that resistance to CA4P was indeed maintained in vivo, since markers of apoptosis, namely DNA fragmentation and cleaved caspase-3 expression were significantly greater in SW1222…”
Section: Discussionmentioning
confidence: 99%
“…Mitotic-arrested cells subsequently undergo mitotic catastrophe and apoptosis through caspase-dependent and -independent mechanisms. In vivo, the plasma half-life of the active CA4 is short 11,29 and it is difficult to predict whether drug exposures are great enough for significant direct cytotoxic effects to occur under these conditions, especially as there may be a degree of drug trapping within tumor tissue, as a consequence of vascular collapse. To maximize efficacy and achieve local tumor control, it is necessary to combine vascular disrupting agents with other therapeutic approaches such as conventional chemotherapy or radiotherapy.…”
mentioning
confidence: 99%
“…It is a synthetic, phosphorylated prodrug of combretastatin A1 (OXi4500), a naturally occurring derivative from the bark of the South African bush willow tree, Combretum caffrum, that reversibly binds to the b-subunit at the colchicine-binding site of tubulin to inhibit microtubule assembly (3,4). It is metabolized to a reactive orthoquinone species that is also assumed to be directly cytotoxic in tumor cells (5,6) because of the production of a quinone metabolite that could bind to nucleic acids and also produces free radicals leading to the enhancement of oxidative stress (7).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that dephosphorylation of CA4P into its active form, CA4, occurs relatively faster (Tozer et al, 1999), whereas glucuronidation of CA4 is much slower in tumor tissues than in plasma (Rustin et al, 2003;Kirwan et al, 2004). This makes CA4P preferentially target tumors.…”
Section: Discussionmentioning
confidence: 99%